2020
DOI: 10.1080/10942912.2020.1770787
|View full text |Cite
|
Sign up to set email alerts
|

Structural characteristics and antioxidant activity of polysaccharide-iron complex from Glehniae Radix

Abstract: The preparation conditions of Glehniae Radix polysaccharide-iron complex (GLP80-Fe) were optimized and the physicochemical properties were characterized by Ultraviolet-visible spectroscopy (UV-Vis), Fourier Transform Infrared Spectroscopy (FT-IR), X-ray diffraction (XRD), Transmission electron microscope (TEM), Thermogravimetric analyzer, and Differential scanning calorimetry (TGA-DSC), respectively. The stability and reducibility of GLP80 and GLP80-Fe were analyzed, and the monosaccharide composition was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…The absorption peak at 760 cm −1 showed that the polysaccharide contained glucose pyranose rings, 11 the result was consistent with previous studies. 12,13 Overall, all the 10 samples had the characteristic absorption peaks of polysaccharides, and the distribution of absorption peaks was similar.…”
Section: The Components and Yields Of Glpsmentioning
confidence: 82%
“…The absorption peak at 760 cm −1 showed that the polysaccharide contained glucose pyranose rings, 11 the result was consistent with previous studies. 12,13 Overall, all the 10 samples had the characteristic absorption peaks of polysaccharides, and the distribution of absorption peaks was similar.…”
Section: The Components and Yields Of Glpsmentioning
confidence: 82%
“…The thermal properties of BCP were analyzed by TGA (Perkin–Elmer, Waltham, Massachusetts, USA) and DSC (Q2000, TA, New Castle, PA, USA). In the TGA test, a 10 mg of sample was placed in an aluminum pan and heated from 25 to 600 °C at a rate of 10 °C/min in N 2 atmosphere [ 35 ]. In the DSC test, 10 mg of sample was heated from 25 to 200 °C at a rate of 10 °C/min under N 2 atmosphere [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…This indicated that the increase of PIC activity should be related to iron chelation and the increase of content. This may be due to the change of the space structure of polysaccharide after it was combined with iron, and the coordination part cooperates with the exposed active groups to promote the interaction with free radicals, thus enhancing the ability of scavenging free radicals (80). However, Wang et al (91) prepared Rosa roxburghii polysaccharide iron complex and found that its antioxidant activity was lower than that of the original polysaccharide.…”
Section: Study On Structure-activity Relationship Of Picmentioning
confidence: 99%